State Policy in the Field of Scientific Activity Management in Turkey - M. Kh. Bogadyrova (Informaciâ i Innovacii)
The article evaluates the scientific and technical policy of Turkey over the past two decades. National trends in research and development (R & D) expenditures, publication products, and patent data were examined for the implications of science and technology policies between 2000 and 2020. The article also provides some conclusions about the results of policy measures in terms of R & D costs and publication output.